Πλατώνειά τε καὶ Σωκράτεια: Identity and Communion in the Heart of Late Hellenism Platonic Communities - Alviz Fernández, Marco (ARYS. Antigüedad: Religiones y Sociedades, 2021)
In this article I aim at analysing the celebrations in honour of the anniversary of Plato and Socrates (Πλατώνειά καὶ Σωκράτεια) within the Platonic communities of late Hellenism. The literary evidence that we have can be dated between the 1st and 5th centuries CE and, as we show in this study, they stand out for its cultural, cultic and ritual character. Regarding the modus operandi, the school leader hosted the special meeting and summoned the inner circle of disciples or companions. They enjoyed altogether a banquet, as well as the literate activities typical of the symposium. In short, it was a celebration permeated by a deeply religious and spiritual atmosphere that became one of the last private pagan practices in Late Antiquity.
Keywords: anniversary; birthday; charisma; Neoplatonism; philosophy; Plato; Socrates